Accuracy of home versus ambulatory blood pressure monitoring in the diagnosis of white-coat and masked hypertension. Issue 8 (August 2015) - Kang, Yuan-Yuan; Li, Yan; Huang, Qi-Fang; Song, Jie; Shan, Xiao-Li; Dou, Yu; Xu, Xin-Juan; Chen, Shou-Hong; Wang, Ji-Guang
<x xml:space="preserve">Abstract</x> Background: We investigated accuracy of home blood pressure (BP) monitoring in the diagnosis of white-coat and masked hypertension in comparison with ambulatory BP monitoring. Methods: Our study participants were enrolled in the China Ambulatory and Home BP Registry, and underwent clinic, home, and 24-h ambulatory BP measurements. We defined white-coat hypertension as an elevated clinic SBP/DBP (≥140/90 mmHg) and a normal 24-h ambulatory (<130/80 mmHg) or home SBP/DBP (<135/85 mmHg), and masked hypertension as a normal clinic SBP/DBP (<140/90 mmHg) and an elevated 24-h ambulatory (≥130/80 mmHg) or home SBP/DBP (≥135/85 mmHg). Results: In untreated patients (n = 573), the prevalence of white-coat hypertension (13.1 vs. 19.9%), masked hypertension (17.8 vs. 13.1%), and sustained hypertension (46.4 vs. 39.6%) significantly (P ⩽ 0.02) differed between 24-h ambulatory and home BP monitoring. In treated patients (n = 1201), only the prevalence of masked hypertension differed significantly (18.7 vs. 14.5%; P = 0.005). Regardless of the treatment status, home compared with 24-h ambulatory BP had low sensitivity (range 47–74%), but high specificity (86–94%), and accordingly low positive (41–87%), but high negative predictive values (80–94%), and had moderate diagnostic agreement (82–85%) and Kappa statistic (0.41–0.66). In untreated and treated patients, age advancing was associated with a higher prevalence of white-coat hypertension and a lower prevalence of masked hypertension defined by 24-h ambulatory (P ⩽ 0.03) but not home BP (P ≥ 0.10). Conclusion: Home BP monitoring has high specificity, but low sensitivity in the diagnosis of white-coat and masked hypertension, and may therefore behave as a complementary to, but not a replacement of, ambulatory BP monitoring.